Nurses’ knowledge regarding nursing care and management of hypertensive patients in a selected hospital in Dhaka city - Begum, Shima; Akter Halim, Khondoker Mahmuda; Islam, Sharmin; Khatun, Ratna; Muhammad, Faisal (International Journal of Research in Medical Sciences, 2019)
Background: Heart diseases, hypertension, diabetes, COPD and cancer are some of the major NCDs and account for more than three-fifths of a death in Bangladesh. This study was aimed to assess the level of nurses’ knowledge regarding nursing care and management of the hypertensive patients. Methods: This study utilized a descriptive cross-sectional study type and the data were collected using self-administered questionnaire. The respondents were informed about the purpose of the study to obtain their consent and they were given clear instructions on how to fill the questionnaires. All the data were analyzed using Statistical Package for Social Sciences (SPSS) version 22. Results: In this study slightly above 60.0% of the participants were female and 73% of them were Muslims. More than half (53.0%) of the respondents had B.Sc. in nursing and 51.3% of them had <10 years of service experience. About 70.4% of the respondents had attended a training on hypertension and 92.2% of them knows about normal blood pressure measurement. About 92.2% of the participants knows the causes of hypertension and 82.6% of the respondents mentioned that hypertension management aims to prevent morbidity and mortality and only 39.1% of them knows the recommended diet for people with hypertension. Conclusions: The finding reported that the nurses’ knowledge regarding the management of hypertensive patients and knowledge on hypertension were very good. Developing knowledge among the nurses in relation to hypertension is the key factor to plan for comprehensive nursing care for better prognosis of the patient.